Effects of minor Nd and Er additions on the precipitation evolution and dynamic recrystallization behavior of Mg–6.0Zn–0.5Mn alloy - Bin-Jiang Lv; Sen Wang; Tie-Wei Xu; Feng Guo (Journal of Magnesium and Alloys, 2021)
A new wrought magnesium (Mg) alloy based on Mg–6.0Zn–0.5Mn (ZM60) is developed, which performs excellent combination of high tensile yield strength and good ductility. We investigate the effects of micro-alloying on dynamic precipitation, dynamic recrystallization (DRX) and mechanical properties of ZM60 alloy. The co-addition of minor (0.6 wt%) neodymium (Nd) and (0.3 wt%) erbium (Er) can accelerate the twinning and DRX process of ZM60 alloy at the initial compression deformation stage. The dynamic precipitation process is also accelerated due to Nd and Er co-alloying. Dislocation accumulation disappears and a higher density of rod β1′ precipitates and some thick β2′ precipitates in matrix and fine twins, which inhibits the growth of DRX grains in compressed ZM60–0.6Nd–0.3Er alloy. The as-extruded ZM60–0.6Nd–0.3Er alloy has a yield strength (YS) of 245.8 MPa, ultimate tensile strength (UTS) of 347.2 MPa and elongation (EL) of 16.3%. The yield strength and tensile strength are improved via minor Nd and Er additions due to fine complete DRX grains, second phase particles and high density of precipitates. The grain refinement, weakened reserved working hardening and weakened basal fiber texture improve the elongation of ZM60–0.6Nd–0.3Er alloy.